Global dissemination of parent-child interaction therapy: The perspectives of Dutch trainees. (November 2018) - Niec, Larissa N.; Abrahamse, Mariëlle E.; Egan, Ryan; Coelman, Frederique J.G.; Heiner, Willemine D.
Abstract: Robust evidence of the efficacy of behavioral parent training (BPT) programs for the treatment of childhood conduct problems has led to increasing international dissemination. As BPT programs are transported out of the countries in which they were developed, it is important to consider how barriers to therapist training vary—or do not vary—across countries and cultures in order to determine how the training process may need to be adapted. Using a systematic qualitative approach, we interviewed 75% (18) of all Dutch therapists trained in the BPT program parent-child interaction therapy (PCIT) to explore their perceptions of the PCIT model, training, and acceptability in the Netherlands. Dutch therapists reported numerous positive experiences with PCIT training and the treatment model, but also described significant barriers related to family, therapist, protocol, and agency factors. Therapists' perceptions of barriers to training and implementation overlapped substantially, though not comprehensively, with a sample of PCIT therapists in the US, suggesting that while PCIT training may be transported from the US to the Netherlands, some barriers exist that are not being addressed in the global dissemination. Highlights: Clinicians offer valuable perspectives on the global implementation of behavioral parent training programs. Dutch clinicians perceive parent-child interaction therapy to be an acceptable treatment. Dutch clinicians experience significant barriers to the implementation of PCIT. PCIT trainers must consider ways to address barriers experienced by Dutch and US clinicians.